2020
DOI: 10.1002/pbc.28636
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of gamma‐secretase inhibitor nirogacestat (PF‐03084014) in desmoid tumor: Report of four pediatric/young adult cases

Abstract: Systemic therapy for pediatric desmoid tumors has been challenged by a lack of high‐quality clinical evidence and potential adverse effects. The gamma‐secretase inhibitor nirogacestat has shown promising efficacy in adults. We report four cases of pediatric and young adult desmoid tumor patients (three with familial adenomatous polyposis [FAP] syndrome) who received nirogacestat on compassionate use. After a median of 13.5 months (range 6‐18), three had durable benefit: a complete response (Case 1); a partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The AXIN2 gene is a direct and the least tissue-specific transcriptional target of the Wnt/β-catenin pathway (44). The TGFB2 gene is not known as a direct Wnt target but has been found to be up-regulated by Wnt stimulation, likely in a tissuedependent way (52)(53)(54). As mentioned, we also find the TGFB2 gene up-regulated in human desmoid tumors (Dataset S2).…”
Section: Medical Sciencessupporting
confidence: 62%
“…The AXIN2 gene is a direct and the least tissue-specific transcriptional target of the Wnt/β-catenin pathway (44). The TGFB2 gene is not known as a direct Wnt target but has been found to be up-regulated by Wnt stimulation, likely in a tissuedependent way (52)(53)(54). As mentioned, we also find the TGFB2 gene up-regulated in human desmoid tumors (Dataset S2).…”
Section: Medical Sciencessupporting
confidence: 62%
“…Importantly, Tazemetostat treatment in the Xenopus model induced a rapid measurable response. This contrasts with the timelines towards clinical responses of the tyrosine kinase inhibitor sorafenib (median time 9.6 months) and the gamma-secretase inhibitor Nirogacestat (> 8 months) currently available to patients afflicted with desmoid tumors (Gounder et al, 2018;Takahashi et al, 2020). Also, for both latter cases the actual drug target involved in the beneficial clinical outcome in desmoid tumors remains unknown.…”
Section: Discussionmentioning
confidence: 95%
“…Grade 3 hypophosphatemia (47%) was reported and was attributed to treatment with nirogacestat [ 18 ]. Among 4 pediatric patients with DT, 3 of whom had tumors harboring APC mutations [ 20 ], 3 patients (1 of whom did not have an APC mutation) had durable benefit with nirogacestat treatment. The fourth patient progressed on therapy after an initial PR.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to decreased expression of a number of Notch target genes, including those in the HES family [ 16 ]. Results from recent clinical trials and case studies have indicated that GSIs have clinical activity in patients with DT [ 17 , 18 , 19 , 20 ]. AL101 and AL102 are structurally similar, potent allosteric small molecule inhibitors of gamma secretase (parenterally and orally administered, respectively) that abrogate activation of all 4 human Notch receptors [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%